Demographic futurity: How statistical assumption politics shape immigration policy rationales in Germany. (August 2019) - Schultz, Susanne
Population projections about 'ageing' or 'shrinking nations' are an important reference for public policies in Europe. The article contributes to the analysis of processes of demographization by showing that speculative future knowledge influences current immigration policy rationales. A theoretical approach to demographic rationalities within global bio/necropolitics is combined with a detailed Social Science and Technology Studies analysis of statistical knowledge production, with reference to the case of Germany. First the concept of demographization is introduced, highlighting the reductionist population-resources epistemology, methodological nationalism, the opaque combination of quantitative and racist/classist qualitative criteria, and the dimension of futurity involved. The author then compares population projections of the EU and the German statistical offices, and unpacks different underlying statistical assumption politics on future net migration. An analysis of the strategic political use of the projections follows: different demographic markers are referred to, depending on whether the projections serve as reference points for racist agendas of closed borders or for neoliberal labour recruitment strategies. The paradoxical functions of the projections, either as forecasts or as what-if-scenarios, are addressed. Finally the author suggests further research on hegemony-building, and argues that the study of demographized immigration policies within the Global North should be integrated into global population policy studies.